USE OF MOTHER TONGUE INTEACHING-LEARNING PROCESS:PERSPECTIVE FROM STUDENT TEACHERS - Baviskar, Chandrakant R.; Pardeshi, Renuka A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The mother language is highly valuable for several reasons. It plays a crucial role in shaping a person’s thoughts and emotions. For a child’s overall development, learning to speak their mother language is essential. Fluency in their native language benefits children in various ways; it connects them to their culture, promotes cognitive development, and facilitates the learning of additional languages.Children begin to understand the world around them through the language they hear from their mothers, starting before they are even born and continuing throughout their lives. Unfortunately, many children in developing regions receive very little effective instruction in school. This lack of comprehension is often due to teaching being conducted in a language they do not fully understand. Such practices can lead to limited learning outcomes, alienating experiences, and high rates of dropout and repetition in education.This article aims to highlight the important views of student teachers of Goa Education College and the importance and role of the Mother language in the teaching-learning process.To improve the quality of education, language policies must prioritize mother-tongue learning. Educational models that ignore the mother language during early years can be unproductive and detrimental to children’s learning. Implementing mother-tongue education, especially in the early stages, allows teachers to instruct more effectively and enables learners to grasp concepts more easily.